Patient-initiated delay at a genitourinary medicine clinic: are there public health consequences?. Issue 7 (23rd September 2008) - Sanmani, L; Foley, E; Samraj, S; Rowen, D; Yadegarfar, G; Patel, R
Abstract : Objectives: To assess the public health consequence of patients electing not to be seen within 48 hours in a genitourinary medicine (GUM) clinic. Methods: A 3-month retrospective case notes review was carried out for 310 new and re-book patients who chose to wait for more than 48 hours to be seen. Results: Altogether, 10% (310/3110) of patients opted to be seen beyond 48 h. Their median wait was 6 days including weekends and 4 days excluding weekends. Demographic details did not vary except for the male to female ratio of 1:1.7 (1:1 in patients seen within 48 h). We found that no symptomatic patients or asymptomatic contacts of those with known sexually transmitted infections (STIs) reported sex with a new partner after booking their appointment. No patient reported sex with a recently treated partner who consequently required re-treatment and none suffered a complication of a STI. In addition, there were no cases of new HIV infection in this group and the rates of STIs were similar compared with patients seen within 48 hours of contacting the unit. Conclusions: Despite 10% of patients choosing to delay attendance beyond 48 h, no adverse public health outcomes were demonstrated.